Development and study on properties of tea flower soap - ZHANG Dan; LU Ying; LI Bo; YU Huajun; TU Youying (浙江大学学报. 农业与生命科学版, 2016)
Compared with tea, tea flower has similar composition and biological activities. Tea flower is rich in polysaccharide, which is regarded as a ‘natural moisturizing factor’. Because of the effect of moisturizing and bacteriostasis, it can be used for improving the moisturizing properties of cosmetic products. The polyphenols and flavonoids from the tea flower have antibacterial, ant-i allergic, and UV resistant function, and can inhibit oxidase lipid peroxidation. They also can inhibit the formation of free radicals and melanin. The saponin from the tea flower has strong effect of emulsification, dispersion, solubility, foaming, cleaning and many other kinds of active function on surface. In addition, tea flower has special honey fragrance, so that it can be used as natural spice products.Tea flower can be used in daily chemical products industry. Three factors and three levels orthogonal analysis were used to select the formula of tea flower soap. The three independent variables are the types of soap material, tea flower powder additive amount, and tea flower petal additive amount. And the quality of tea flower soap was valued from skin care, sensory indexes. The results showed that the best components in soap were weakly-alkaline soap material and 2% tea flower powder, which make the soap white with a little yellow and have tea flower fragrance. The skin test on the dorsum of hand showed that the usage of tea flower soap can decrease oil contents by 49% and pigment contents by 20%, while increasing water contents in dermal layer by 51%, elasticity by 36% and collagen fiber contents by 9%. By expanding experiment, it was found that the tea flower extracts can further improve the performance of product.This study developed a natural tea flower soap with strong abilities of cleaning and protecting skin. It also provides scientific theoretical basis for tea flower’s application in daily chemical products and a new way for the comprehensive utilization of Camellia resources.